Sebaran Batuan Karbonat Di Cekungan Matarombeo, Lengan Tenggara Sulawesi - Samodra, Saptono Budi; surjono, sugeng sapto (Geosfera: Jurnal Penelitian Geografi, 2024)
Carbonate rocks, especially reef, are an exploration target for sedimentary basins that are still beginning to be explored. In the Matarombeo Basin, there are 5 rock formations composed of carbonate rocks, namely the Tokala Formation, Matano Formation, Tampakura Formation, Eomoiko Formation and Buara Formation. The aims of this research are to determine the distribution of the five carbonate rock formations and their potential as hydrocarbon reservoirs in the study area.. The data used is data from surface geological investigations and seismic data. From the analysis results it is known that carbonate rocks from the Tampakura Formation and the Eomoiko Formation can function as the main reservoir in the Matarombeo Basin. This is based on the physical properties of the rock which has fairly good porosity and permeability, and can be easily recognized in seismic sections as reef growth. The existence of reefs that grow at heights and are connected to the interior which can function as a kitchen area causes the limestone of the Tampakura Formation and the Eomoiko Formation to become the main reservoir targets in the Matarombeo Basin.